Influenza-like Illness in Households with Children of Preschool Age. Issue 3 (March 2016) - Mughini-Gras, Lapo; Pijnacker, Roan; Enserink, Remko; Heusinkveld, Moniek; van der Hoek, Wim; van Pelt, Wilfrid
Abstract : Background: Influenza-like illness (ILI) is the leading cause of medical consultation amongst preschool children, who may contribute to spreading ILI-causing agents within the household. We aimed to determine the societal burden (incidence, health-care consumption and productivity loss) and correlates of ILI in households with preschool children. Methods: A survey was performed in the Netherlands during October 2012 to October 2014. Monthly, 2000 households with children younger than 4 years were invited to report their symptoms and related medical care, productivity loss and putative risk exposures for 1 preschool child and 1 parent. Results: Eight thousand seven hundred and sixty-eight child–parent pairs were enrolled. ILI incidence was 2.81 episodes/child-year and 1.72 episodes/parent-year. Amongst those with ILI, health-care utilization was 35.7% (children) and 17.7% (parents). Work absenteeism was 45.7% (median 2 workdays lost) and day-care absenteeism was 22.8% (median 1 day missed). Chronic respiratory conditions, developmental disabilities, parental occupation in health care/child care, having a sibling and attending day care for ⩽12 months increased childhood ILI risk. Parental ILI risk increased with having chronic respiratory conditions, developmentally disabled day-care–attending children and female gender in interaction with unemployment and multiple day-care–attending children. Breastfeeding infants 6-month-old or younger and attending day care for >24 months decreased childhood ILI risk. Pregnancy, occupation in health care and having ≥3 children decreased parental ILI risk. Parents of ILI-affected children had a concurrent 4-fold higher ILI risk. Conclusion: ILI in households with preschool children has a considerable societal impact. Risk-mitigating initiatives seem justified for day-care attendees, mothers, people with chronic respiratory conditions, and children with developmental disabilities. Children attending day care for >2 years acquire some protection to ILI. Abstract : Supplemental Digital Content is available in the text.